GENDER DAN KOMUNIKASI POLITIK AKTIVIS PARTAI ISLAM DI PADANG SUMATERA BARAT - pohan, alqanitah (Universitas Islam Negeri Imam Bonjol Padang, 2007)
Affirmative action in gender mainstreaming at politic party, is marked with theexistence of quota 30% women role in nomination quota of legislative memberinviting pro and contra. There are two perspectives in looking at this gender. First, positivistic perspective (or objective) which sees that women have to begiven opportunity in political space, its importance if women to have make ofpolicy. Proper women isn t it well-balance position with men in legislativebecause amount residents of more women compared to men. Second the naturalistic perspective (or subjective). Which my tries to express that women have their own responsible and their readiness of women to enter political world